Orchids and emonocot - assembling research resources and facilitating collaborative taxonomy online - Gardiner, Lauren M.; Bone, Ruth; Kilgallen, Niamh M. (Lankesteriana: International Journal on Orchidology, 2013)
The Orchidaceae is one of the eight families targeted for in-depth treatment in the groundbreaking eMonocot project. A consortium formed by RBG Kew, the Natural History Museum (London), and Oxford University, and funded by NERC, eMonocot is an e-taxonomy initiative that will provide the first web-based treatment for the world’s monocot plants (constituting approximately 20% of all higher plants, some 70,000 species, and including numerous groups of the highest conservation, ecological, and economic importance). eMonocot will revolutionize the way taxonomic data are organized and accessed by both the practitioners and users of taxonomy, targeted at biodiversity and environmental scientists but also available to other users including volunteer biologists, horticulturists, schools, and the general public. Available information will include nomenclature, taxonomic descriptions, images, identification guides, as well as geographical, ecological, DNA sequence, and conservation data structured around a taxonomy derived from the World Checklist of Monocotyledons. As part of the eMonocot project, identification guides, and taxon pages to all Orchidaceae genera will be produced, alongside an interactive key and taxon pages for all Cypripedioideae (slipper orchid) species and infra-specific taxa. Researchers may upload content (such as images and species descriptions) to the taxon pages, edit the classification as taxa are described and revised, and access original publications for names and much more.